Faktor-Faktor Yang Mempengaruhi Return Bagi Hasil Deposito Mudharabah (Studi Empiris Pada Bank Umum Syariah Di Indonesia Tahun 2012-2016) - Khairul Umuri; Endang Ahmad Yani; Abdi Triyanto (JURNAL EKONOMI DAN PERBANKAN SYARIAH, 2018)
This research aims to test the influence of Financing to Deposit Ratio (FDR), Non-Performing Financing (NPF), and operating income against operating expenses return for the results on the Mudharabah deposit a public Bank Syariah 2012-2016 period. The object of this research is full-fledged Islamic Bank in Indonesia. Sampling is done by purposive sampling technique so that the retrieved 9 samples of full- fledged Islamic Banks during period 2012-2016. Methods of analysis used in this study was multiple linear regression using panel data that help by using Eviews9. The results of this study indicate that simultaneously independent variable has no effect significantly to the rare of profit sharing deposito mudharaba in islamic bank. While partially, FDR and the NPF has no effect significantly to the rare of profit sharing deposito mudharaba in islamic bank, and BOPO has positive significantly effect to the rare of profit sharing deposito mudharaba in islamic bank.